Innovative approach to safely induce controlled lipolysis by superparamagnetic iron oxide nanoparticles-mediated hyperthermic treatment. (December 2017) - Marinozzi, Maria Rosaria; Pandolfi, Laura; Malatesta, Manuela; Colombo, Miriam; Collico, Veronica; Lievens, Patricia Marie-Jeanne; Tambalo, Stefano; Lasconi, Chiara; Vurro, Federica; Boschi, Federico; Mannucci, Silvia; Sbarbati, Andrea; et al.
Graphical abstract: Abstract: During last years, evidence has been provided on the involvement of overweight and obesity in the pathogenesis and aggravation of several life-threatening diseases. Here, we demonstrate that, under appropriate administration conditions, polyhedral iron oxide nanoparticles are efficiently and safely taken up by 3T3 cell line-derived adipocytes (3T3 adipocytes) in vitro. Since these nanoparticles proved to effectively produce heat when subjected to alternating magnetic field, 3T3 adipocytes were submitted to superparamagnetic iron oxide nanoparticles-mediated hyperthermia treatment (SMHT), with the aim of modulating their lipid content. Notably, the treatment resulted in a significant delipidation persisting for at least 24 h, and in the absence of cell death, damage or dedifferentiation. Interestingly, transcript expression of adipose triglyceride lipase (ATGL), a key gene involved in canonical lipolysis, was not modulated upon SMHT, suggesting the involvement of a novel/alternative mechanism in the effective lipolysis observed. By applying the same experimental conditions successfully used for 3T3 adipocytes, SMHT was able to induce delipidation also in primary cultures of human adipose-derived adult stem cells. The success of this pioneering approach in vitro opens promising perspectives for the application of SMHT in vivo as an innovative safe and physiologically mild strategy against obesity, potentially useful in association with balanced diet and healthy lifestyle.